2018
DOI: 10.24042/alidarah.v8i1.3078
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Disiplin Kerja Terhadap Kinerja Guru MTS Se- Kota Bandar Lampung

Abstract: Teachers’ performance is one of the factors that is necessary to organize theexcellent education and learning. Teachers’ performance improvement effortis influenced by many factors, including discipline of work. The problem isdiscipline of work is not be a culture of school academic. The method used inthis research was a quantitative method with survey approach and thelocation of this reserch is at MTs around Bandar Lampung with 82 personsof respondences chosen as the sample. Research result shows that discipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
3
0
7
Order By: Relevance
“…53 Tahun 2010 sebaga sikap atau perilaku seseorang dalam melaksanakan kewajiban serta tidak melanggar aturan sesuai peraturan yang ada. Dengan memandang guru sebagai bagian komponen SDM, tentu tingkat kedisiplinan guru di tempat bekerja menjadi faktor yang sangat berpengaruh dalam menentukan keberhasilan kinerja guru tersebut dalam menjalankan peranannya di sekolah (Hadiati, 2018).…”
Section: Pendahuluanunclassified
“…53 Tahun 2010 sebaga sikap atau perilaku seseorang dalam melaksanakan kewajiban serta tidak melanggar aturan sesuai peraturan yang ada. Dengan memandang guru sebagai bagian komponen SDM, tentu tingkat kedisiplinan guru di tempat bekerja menjadi faktor yang sangat berpengaruh dalam menentukan keberhasilan kinerja guru tersebut dalam menjalankan peranannya di sekolah (Hadiati, 2018).…”
Section: Pendahuluanunclassified
“…Kinerja guru merupakan segala bentuk perilaku, kegiatan hingga hasil yang dilakukan dan dihasilkan di tempat kerja (Darma, 2019). Kinerja karyawan sangat mempengaruhi mutu hasil pekerjaan yang dihasilkan baik pada jangka pendek juga jangka panjang (Hadiati, 2018).…”
Section: Landasan Teori Dan Pengembangan Hipotesisunclassified
“…Hadiati's research The Effect of Work Discipline on MTs Performance in Paddy Lampung states that, based on the results of the presentation and analysis of the data, it is concluded that the work discipline has a positive and important impact on the performance of MTs in Paddy Lampung [22].…”
Section: The Effect Of the Teaching Discipline On The Output Of Teachersmentioning
confidence: 99%